Preliminary Validation of a Student Digital Literacy Questionnaire Based on the UNESCO Digital Literacy Global Framework and DigComp 2.2 - Barrios, Rubilyn G; Dosol-Demonteverde , Mailah Grace; Kurnia, Nova; Sharov, Sergii (International Journal of Essential Competencies in Education, 2026)
This study aims to examine the preliminary validation of a Student Digital Literacy Questionnaire based on the UNESCO Digital Literacy Global Framework and DigComp 2.2. The instrument was developed to measure seven dimensions of digital literacy: device and digital application operation, information and data literacy, digital communication and collaboration, digital content creation, digital safety and ethics, digital problem solving, and digital use for learning. This study employed a quantitative approach involving 350 respondents. Data were analyzed using descriptive statistics, the Kaiser-Meyer-Olkin Measure of Sampling Adequacy, Bartlett’s Test of Sphericity, exploratory factor analysis, corrected item-total correlation, Cronbach’s Alpha, and a specified CFA measurement model. The results showed that the mean student digital literacy score was 116.18, indicating a moderate-to-high tendency. The KMO value of 0.951 and significant Bartlett’s Test at p < 0.001 indicated that the data were suitable for factor analysis. Factor extraction produced seven factors with a cumulative variance of 47.04%. All items were valid, with corrected item-total correlations ranging from 0.412 to 0.548. The overall reliability was very high, with a Cronbach’s Alpha of 0.924, while dimensional reliability ranged from 0.638 to 0.690. The CFA model was specified as a higher-order measurement model with seven first-order latent factors. The instrument is considered suitable as a preliminary measure of students’ overall digital literacy in the context of school-based digital learning.